The Stanwick Fortifications, North Riding of Yorkshire - Wheeler, Sir, Mortimer (Reports of the Research Committee of the Society of Antiquaries of London, 1954)
This is an account of the excavations of the Stanwick fortifications in North Yorkshire, England, undertaken in 1951-2. Included are descriptions of human remains and artefacts such as pottery, weaponry and metalwork, together with an account of the methodology used to unearth these.